Marc Brown Arthur chapter book : Buster's dino dilemma Vol.7 - Brown, Marc Tolon (Boston, Mass. Little, Brown, 1998)
When Arthur's third-grade class goes hunting for fossils at Rainbow Rock State Park, his friend Buster actually finds one, and instead of turning it in Buster decides to take it home--but he soon regrets his decision.
"RL 3.1"--P. [4] of cover.
Keywords: Fossils -- Fiction; Rabbits -- Fiction; Aardvark -- Fiction